IgG4 Level in Thyroid Diseases - Kirdok, Kutay; Ozdemir, Nilufer; Guney, Sedat Can; Ecemis, Talat; Hekimsoy, Zeliha (Hormone and Metabolic Research, 2025)
Immunoglobulin G4 (IgG4)-related diseases are a group of inflammatory conditions in which antibodies against IgG4 play a major role. IgG4-related diseases can affect thyroid gland. Our aim was to investigate whether there is a difference in IgG4 levels among different thyroid disease groups and to examine the relationship between IgG4 levels and thyroid function tests, thyroid autoantibodies and thyroid volume. Our study included 151 patients and 48 healthy volunteers. The patients were divided into groups such as Graves’ disease, Hashimoto’s thyroiditis, autoantibody negative thyroid nodules, and control group. These four main groups were subdivided according to IgG4 level and IgG4/IgG ratio and included in the statistical evaluation. There was no statistically significant difference between IgG4 and IgG4/IgG ratio in four main groups. The free T3, T4, and Hertel values in Graves’ disease group were statistically significantly higher in the groups with IgG4≥135 mg/dl and IgG4/IgG ratio≥8%. Our study suggests that IgG4 may play an important role in the pathology of thyroid diseases and its elevation may exacerbate the course of Graves’ disease and Graves’ ophthalmopathy. Further research is needed to elucidate the clinical implications of IgG4 in thyroid disease management and progression.
Keywords: IgG4; IgG4/IgG ratio; IgG4 related diseases; autoimmune thyroid disease; Graves’ ophthalmopathy; Hertel value